Start with why: how great leaders inspire everyone to take action by Simon Sinek - Sousa, Ivo Dias de (2016)
Recensão crítica à obra de Simon Sinek, "Start With Why: How Great Leaders Inspire Everyone To Take Action". New York: Penguin, 2011